Analysis and Optimization of Ecological Network Change in Guangxi Beibu Gulf Economic Zone - LI Yiyun, LING Ziyan, JIANG Weiguo, WU Juncheng (Journal of Geodesy and Geoinformation Science)
With the continuous acceleration of urbanization, the resulting habitat fragmentation poses a serious threat to regional ecological security. Constructing an ecological network not only facilitates the positive circulation of regional materials and energy but also holds significant importance for achieving regional sustainable development. Taking the Guangxi Beibu Gulf Economic Zone as the study area, and supported by GIS and other technologies, this study uses 10-meter high-resolution land use data from 2017 and 2021 to select ecological sources based on MSPA and landscape connectivity. Using the MCR-gravity model, a higher precision ecological network for the Guangxi Beibu Gulf Economic Zone is constructed. This network is then optimized and comparatively analyzed using circuit theory and network analysis methods. The results showed that: ① Although the core area of ecological sources accounts for 95.16% of the total ecological source area, a comparison of the two-year analysis results shows an increasing degree of landscape fragmentation and a decline in landscape connectivity. ② The optimized ecological network of the Beibu Gulf Economic Zone of Guangxi comprises 11 ecological sources, 91 ecological corridors, and 71 ecological nodes. ③ The indices of the optimized network structure have all improved, enhancing the degree of ecological network connectivity within the study area.